Transient Thermal Stresses Analysis in a FPGM Cylinder - Nabard Habibi; Sadi Samawati; Omid Ahmadi (Mechanics of Advanced Composite Structures)
The present study aims to investigate the analysis of stress, strain, displacement, and electrical potential of a thick hollow cylinder made of FGPM under mechanical and thermal loads. Distribution of mechanical property of material is considered along the shell stick through the power distribution function. Thermal loads have been taken to signify the difference of temperature between outer and inner surfaces for each type of mechanical property. After extracting and solving the differential equations in transient state and the observation of mechanical and thermal boundary conditions, governing functions are obtained through the following parameters: thermal conduction non-homogeneous parameters, thermal linear distribution coefficient, elastic stiffness constant, piezo-electric coefficient, and dielectric constants.